Trzynastowieczne święte kobiety kręgu franciszkańskiego z Polski i Czech – kształtowanie się i rozwój kultu w średniowieczu - Krzyżostaniak, Hanna (My University, 2010)
Praca omawia średniowieczny rozwój kobiecych kultów kształtujących się w XIII i XIV wieku po śmierci pięciu księżnych, wybitnych promotorek duchowości franciszkańskiej w Europie Środkowej: Salomei, Kingi, Jolenty-Heleny, Agnieszki z Pragi oraz Anny. Rozważania rozpoczyna zestawienie tradycji kultu świętych na terenach państw, do których ograniczono dociekania (Polski i Czech), ze szczególnym uwzględnieniem problemu świętości kobiecej. Kolejną część pracy otwiera krótkie przedstawienie bohaterek, których kulty stanowią temat rozprawy, wraz z omówieniem specyfiki duchowości XIII wieku - ważnych aspektów życia religijnego, nadających kształt postawom polskich i czeskich pań, tudzież wpłynąć na kształtowanie się opinii o ich świętości.Rozdział trzeci jest omówieniem najwcześniejszego etapu kultu (poszczególnych przejawów czci, jaką otoczono zmarłe księżne), którego początek wyznacza śmierć bohaterek rozprawy, a koniec powstanie najstarszych tekstów hagiograficznych, stanowiących podsumowanie tej fazy procesu. Przedmiotem dalszej części pracy są teksty hagiograficzne będące wyrazem pewnej dojrzałości kultu (pytania o czas powstania tych dzieł, autorstwo oraz sposób redagowania tekstów, profil hagiograficzny, grono inspiratorów i odbiorców) a których powstanie można wiązać z zamysłem starań o kanonizację (na podstawie zachowanych tekstów omówiono szerzej zabiegi o wyniesienie na ołtarze Agnieszki Czeskiej). Punktem wyjścia dla rozdziału V „W kierunku zaniku czy rozwoju?” jest omówienie rozpowszechnienia się opinii o świętości kobiet i przejawów kultu w późniejszym średniowieczu, czy wreszcie kolejnych starań o kanonizację.Ostatni z rozdziałów wyłączony został z porządku chronologicznego, gdyż zbiera wiadomości o społecznościach promujących kult, a także o tym, skąd rekrutowali się czciciele świątobliwych pań.

The thesis is to present results of the research done on different aspects of the phenomena mentioned in topic – the cults of saint women from specific, West-European area. The women who are to be the subject of this analyze came from royal houses. Salome was the daughter of Leszek the White, of Piast dynasty; Cunegond and Yoland (sisters) came from Hungarian Arpads, however through the dynastic marriages became Princesses of Lesser and Great Poland. Another two women: Agnes and Ann were daughters of Ottokar I, the King of Bohemia. While the first took the religious vows and became the nun of Saint Claire, the second ruled in Silesia, as a wife of Henry II the Pious.By reason of appearing two names of countries: Poland and Bohemia in the title of the thesis, one can learn that this analyze is a comparative one. Introduction to this problem should be a chapter which will show history of the phenomenon of the cult of saints in both countries.The author’s next step is a short presentation of the pious ladies, with some special emphasis on their religiosity of a new type, which was following Christ (imitatio Christi). This trend derived from Saint Francis, Saint Claire and what is particularly significant – Saint Elisabeth of Hungary who was related to all the polish-bohemian princesses.The thesis mostly presents consecutive stages of the process of development of the cult. The first step is to trace all the religious practices which started at the moment of death (nativitas spiritualis): the veneration of a grave, pilgrimages, the cult of relics, the practice of reporting on miracles. We can say that this first stage of spontaneous cult resulted in drafting first hagiographical biographies of the women. The other chapter (IV) tackles two problems: the context in which the legends were written and attempts to obtain canonical permission to venerate the mentioned persons.Unfortunately none of those women was canonized in the Middle Ages so a question might be asked what forms those veneration took later – did they tend to develop (even without papal approval) or limit their range to cloisters (V chapter).Last chapter (VI), which is out of the chronologic order in comparison to previous ones, investigates so-called social aspect of these cults. Firstly, I am interested in the promoters of the veneration. The dynastic, noble and finally monastic circles are examined. The other question is which social groups participated in all religious practices that were already mentioned.
The Franciscan Saint Women of Poland and Bohemia from Thirteenth Century – the Origins and Development of their Cult in the Middle Ages
Wydział Historyczny: Instytut Historii
Keywords: Świętość; Sainthood; Kult; Cult; Franciszkanizm; Franciscanism; Kobiety; Women; Historia Kościoła; Church History; Średniowiecze; Middle Ages